BIBLIOMETRIC ANALYSIS ON CIVIL SERVANT (ASN) PERFORMANCE USING VOSVIEWER - Widaningsih, Widaningsih; Purwana, Bayu Hikmat; Sinurat, Henri Prianto (Puslatbang KHAN, 2024)
Civil Servant (ASN) Performance has been the main focus of the Government of Indonesia as a part of ASN’s main role as a motor of national development. Studies have shown interrelations of ASN Performance into many aspects including achieving organizational goals, gaining public trust, and providing an accessible and optimal public service. This research aims to develop a conceptual framework of ASN Performance by utilizing VOSViewer to analyze research publication trends indexed in Dimensions and mapped in three different visualizations: network visualization, overlay visualization and density visualization. The result of the study shows that research on ASN Performance experienced fluctuations as a result of various factors including government policy, Covid-19 Pandemic and bureaucracy reform. ASN Performance is closely interrelated to various areas such as merit system, motivation, work discipline, human resources management, organizational culture, and supervision. A research on the influence of individual motivation and organizational climate to ASN Performance is the most cited article in the span of 2016-2023. Findings of this results contributes to future efforts in improving ASN performance by providing general overview of topics related to it that are actively researched, discussed, aiming to ensure quality of public services.